Amylin receptor activation in the ventral tegmental area reduces motivated ingestive behavior. (1st September 2017) - Mietlicki-Baase, Elizabeth G.; McGrath, Lauren E.; Koch-Laskowski, Kieran; Krawczyk, Joanna; Reiner, David J.; Pham, Tram; Nguyen, Chan Tran N.; Turner, Christopher A.; Olivos, Diana R.; Wimmer, Mathieu E.; Schmidt, Heath D.; Hayes, Matthew R.
Abstract: Amylin is produced in the pancreas and the brain, and acts centrally to reduce feeding and body weight. Recent data show that amylin can act in the ventral tegmental area (VTA) to reduce palatable food intake and promote negative energy balance, but the behavioral mechanisms by which these effects occur are not fully understood. The ability of VTA amylin signaling to reduce intake of specific palatable macronutrients (fat or carbohydrate) was tested in rats in several paradigms, including one-bottle acceptance tests, two-bottle choice tests, and a free-choice diet. Data show that VTA amylin receptor activation with the amylin receptor agonist salmon calcitonin (sCT) preferentially and potently reduces intake of fat, with more variable suppression of sucrose intake. Intake of a non-nutritive sweetener is also decreased by intra-VTA administration of sCT. As several feeding-related signals that act in the mesolimbic system also impact motivated behaviors besides feeding, we tested the hypothesis that the suppressive effects of amylin signaling in the VTA extend to other motivationally relevant stimuli. Results show that intra-VTA sCT reduces water intake in response to central administration of the dipsogenic peptide angiotensin II, but has no effect on ad libitum water intake in the absence of food. Importantly, open field and social interaction studies show that VTA amylin signaling does not produce anxiety-like behaviors. Collectively, these findings reveal a novel ability of VTA amylin receptor activation to alter palatable macronutrient intake, and also demonstrate a broader role of VTA amylin signaling for the control of motivated ingestive behaviors beyond feeding. Highlights: VTA amylin receptor activation more potently reduces intake of fat than of sucrose. VTA amylin signaling reduces saccharin intake and stimulated water intake. Effects of VTA amylin on macronutrient intake depend on baseline food preferences. VTA amylin receptor activation does not induce anxiety-like responses.